OBSERVACIONES SOBRE LA FLORA Y VEGETACION DE DOS TURBERAS EN LA REGION DE AISEN, PATAGONIA CHILENA - Teneb, Ernesto; Gómez, Patricia; González, Mariela (Gayana Botánica, 2008)
We report results of flora and vegetation in two of Sphagnum peatbogs in the Aisén Region.